ANALYSIS OF GRAMMATICAL ERRORS ON STUDENTS’ TRANSLATION FROM INDONESIAN INTO ENGLISH MADE BY THE SECOND GRADE STUDENTS - Yanita ulani Silitonga; Nelson Balisar Panjaitan (Jurnal Scientia, 2022)
The purpose of this study was to find out (1) the types of errors in the Indonesian to English translation texts made by class XII students (2) the process of making errors by students, and (3) the reasons for the errors. occurred in students' translation from Indonesian to English. This research is a qualitative research. The subjects of this study were students of class XII. The students consist of 30 students in class XII. The results of this study, the authors found that students made mistakes in the Indonesian to English translation text, the authors found the types of errors and the causes of errors made by students in translating Indonesian to English texts. The types of errors are verb error, preposition error, article error, possessive pronoun error, spelling error. The causes of errors that make students produce errors in translating Indonesian to English are interlingual transfers, intralingual transfers, lack of motivation, developmental errors, and interference errors.